A single case experimental design study on improving social communication skills after traumatic brain injury using communication partner telehealth training. (2nd January 2019) - Rietdijk, Rachael; Power, Emma; Brunner, Melissa; Togher, Leanne
ABSTRACT: Primary objective: To investigate use of telehealth to deliver social communication skills training (TBIconneCT) to people with severe traumatic brain injury (TBI) and their communication partners (CPs). Research design: Feasibility study involving single case experimental design with two participants. Methods and procedures: TBI Express is an established program for improving social interactions between people with TBI and their CPs. To improve access to the program, we developed a modified version called TBIconneCT that can be delivered via videoconferencing. Two participants with TBI and their CPs completed TBIconneCT training. Outcome measures included exchange structure analysis of conversation samples, blinded ratings of conversation samples and self-report measures. Main outcomes and results: The study indicated positive change on blinded ratings of conversation and self-reported measures for both participants. Exchange structure analysis conducted on session-by-session data did not demonstrate treatment effects due to variability during baseline. Conclusion: This study indicated potential for using telehealth to provide social communication skills training to people with TBI and their families. The study findings provide a foundation for a phase one clinical trial which will compare in-person with videoconferencing delivery of TBIconneCT.